Ultrafast-Charging Supercapacitors Based on Corn-Like Titanium Nitride Nanostructures - Yang, Peihua (2017)
Ultrahigh rates realized by ALD-made TiN. The symmetric full-cell supercapacitors deliver a typical capacitance of 20.7 F cm−3 at a scan rate of 1 V s−1, and retain 4.3 F cm−3 at high rate of 100 V s−1. The devices can be charged and discharged for 20 000 cycles with negligible capacitance loss and with an ultralow self-discharge current (≈1 μA).